STUDENT DIFFICULTIES IN SOLVING MATHEMATICS QUESTIONS BASED ON MATHEMATICAL LOGIC INTELLIGENCE DURING THE COVID-19 PANDEMIC - Vera Dewi Susanti; Rika Wulandari (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
This study aims to analyze students' difficulties in solving mathematical problems based on mathematical logic intelligence. The population of this research is the fourth-semester students of Mathematics Education, Universitas PGRI Madiun, totaling 52. While the subjects of this research are 3 students based on mathematical logic intelligence. The subject is taken by one student each from high, medium, and low mathematical logic intelligence. This research is descriptive qualitative research using the triangulation technique. Data collection techniques used are tests, interviews, and documentation. Instruments in the form of advanced mathematical material tests and tests of mathematical logic intelligence. The data analysis technique uses data reduction, data presentation, and conclusion drawing. The conclusion in this study is that subjects who have high mathematical logic intelligence have no difficulty in working on problems, subjects of mathematical logic intelligence are having difficulty at the stage of re-examining their answers, and subjects of low mathematical logic intelligence have difficulty in solving problems properly and have not been able to re-examine the answers. Penelitian ini bertujuan untuk menganalisis kesulitan mahasiswa dalam menyelesaikan soal matematika berdasarkan kecerdasan logika matematika. Populasi penelitian ini mahasiswa semester IV Pendidikan Matematika Universitas PGRI Madiun yang berjumlah 52. Sedangkan subjek penelitian ini adalah 3 mahasiswa berdasarkan kecerdasan logika matematika. Subjek tersebut diambil masing-masing satu mahasiswa dari kecerdasan logika matematika tinggi, sedang dan rendah. Penelitian ini merupakan penelitian kualitatif deskriptif dengan menggunakan triangulasi teknik. Teknik pengumpulan data yang digunakan adalah tes, wawancara dan dokumentasi. Instrumen berupa tes materi matematika lanjut dan tes kecerdasan logika matematika. Teknik analisis data menggunakan reduksi data, penyajian data, penarikan kesimpulan. Kesimpulan pada penelitian ini adalah subjek yang memiliki kecerdasan logika matematika tinggi tidak mengalami kesulitan dalam mengerjakan soal, subjek kecerdasan logika matematika sedang kesulitan pada tahap memeriksa kembali jawabannya dan subjek kecerdasan logika matematika rendah kesulitan dalam menyelesaikan soal dengan baik dan belum mampu memeriksa kembali jawabannya.